Literature Review: Perbandingan Fecal Immunochemical Test dan Fecal Calprotectin dalam Monitoring Pasien Kolitis - Naufal Nathan Arif Hitam; Agung Ary Wibowo; Rahmiati Rahmiati; Hery Poerwosusanta; Dewi Indah Noviana Pratiwi (Homeostasis, 2021)
Abstract: Colitis is a group of inflammatory diseases in colon with frequent of recurrences. Non-invasive detection methods are needed to evaluate inflammatory activity and mucosal healing in order to reduce the risk of recurrence and complications of irreversible tissue damage in colitis. Stool markers such as the fecal immunochemical test (FIT) and fecal calprotectin (Fcal) are an alternative as a simple, inexpensive, and non-invasive test for detecting inflammation in colon. The purpose of this paper is to compare the FIT and Fcal in monitoring colitis patients. This paper was done using the literature review method. Search for articles through the Pubmed and Google Scholar databases using the keyword